The language of Islamophobia in internet articles - Mohamed Ali, Haja Mohideen; Mohideen, Shamimah (IIUM Press, 2008)
Islamophobia, the hatred for and fear of Islam and Muslims, manifests itself physically, politically, culturally and linguistically, besides in other forms. From the linguistic perspective, many words have been coined to perpetuate prejudices against Muslims and Islam. Islam and Muslims are often found in collocational use in the most derogatory and irresponsible way. Islamophobic terms from the internet have been identified for a rational and objective discussion to combat Islamophobic discourse.